(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article is devoted to the presentation of individual author’s language worldview based on the poetic speech material of I. Kotlyarevsky and A. Pushkin. The thematic field “Food” is presented in ten lexical and semantic groups in the poem “Eneida”: “Meat meal”, “Fish dishes”, “First Course”, “Main courses”, “Pastry products”, “Dairy foods”, “Sweet dishes”, “Drinks”, “Vegetables, berries, plant products”, “Dish ingredients". The majority of thematic field “Food” vocabulary belongs to a national Ukrainian Cossack cuisine. Culinary habits are almost the same as among the Gods of Olympus and members of royal families, and as well as among ordinary people. Most of the food is preserved in modern cuisine. Some notions require additional explanation due to their historical status. These terms include teterya, ryabko, lemishka, putra, salamakha (salamat), potaptsi etc. despite the remained recipes of cooking. Among the variety of alcoholic products, mainly of domestic production, some drinks are imported from Germany, including Rhine wine with cardamon. Overseas wine with its rare for the modern reader name is nothing but a Cossack cordials, liqueurs, homemade wine containing fruits from Ukraine and distant countries. Thematic field “Food” is represented by such lexical and semantic groups in the novel in verse “Eugene Onegin”. They are “Meat meal”, “Dairy foods”, “Vegetable dishes”, “Baking”, “Sweet dishes”, “Beverages”. All borrowed from other countries recipes are the part of restaurant menus among St. Petersburg wealthy families. Traditional dishes are more democratic and familiar for squireen and peasants. Some courses are relevant to the modern cuisine. For example, roast, fat, cream, mushrooms, pies, pancakes, bread, berries, fruit liqueurs, roast-beef, beef-steaks, cutlets, truffles, tea, coffee, rum, bacon, pineapples. Exotic to the early nineteenth century dishes are included both in home and restaurant menus. Brew, “Bordeaux”, “Veuve Clicquot”, “Champagne” technology of cooking has been changed over the years. Some of the dishes are retreated into the history of culinary art, such as Strasbourg pie, Lymburhsky cheese. Thematic field “Food” takes the reader to the masters’ works of stylistic expression cultural cognitive mapping. It gives the idea of the gastronomic preferences and habits of the people at those times and the national specifics of the cuisine. It also covers economic, commercial, culinary folk connections, social stratification of society and reveals dishes that changed their recipe in cooking or even became historical.